Globalization in Higher education, Advantage and Disadvantage of Online Education - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2023)
This article was prepared with the support of PADME (Pallas Athéné Domus Meriti). E-learning has many advantages and disadvantages. Among these, I would like to highlight some of the more important ones, as well as present the results of my surveys in which I assessed university students' modeling, abstraction and lexical knowledge before and after online education.